Pengujian Kekerasan Plat Bodi Lori Batubara Dengan Suhu 400C di Quenching Dengan Air Garam - Niharman Niharman; Antonius F A Silaen (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
Abstract The heat treatment process in metals is very useful for obtaining quality metals and having physical properties including better electrical conductivity, microstructure, density and mechanical properties, especially in terms of hardness, elasticity and workmanship of the nature of origin. This process is carried out at a temperature of 4000C for 15 minutes then cooled with a water cooling medium mixed with 200 grams of salt, 400 grams, 600 grams, 800 and 1000 grams. Test results with the value of hardness average results without treatment = 65.2, quenching water mixed with salt 200 grams = 57.8, quenching water mixed with salt 400 grams = 57.36, quenching water mixed with salt 600 grams = 76.48, quenching water mixed with salt 800 grams = 77, quenching water mixed with salt 1000 grams = 58, 42. Specimens that were subjected to heat treatment and quenched with water mixed with 600 grams and 800 grams had an increased hardness value compared to the specimen without receiving treatment, while specimens that received heat treatment of 400ºC with quenching water mixed with 200 grams of salt, 400 grams and 1000 grams had decreased hardness compared to specimens without getting different treatment. Based on the above test it can be concluded that the right amount of salt mixed with water can increase the dryness value in the specimen to be tested